O Papel da Medicina Regenerativa no tratamento e reabilitação de lesões desportivas - Diana Cristina Pinto Guedes (2021)
The surgeon's role in orthopedic lesions repair has been traditionally associated with restoring lost function through the optimization of the lesion's biomechanical environment. It is known, however, that the observed lesions in this particular field display a weak spontaneous recovery potential and that the available techniques until recently ended up resulting in irrecoverable deficits or lengthy recovery periods. Significant improvements over the past two decades in sports lesions' approach and treatment can be attributed to the development of minimally invasive techniques and more guided rehabilitation programs. All this new knowledge has provided a gateway for new biological therapies, notably Platelet-rich Plasma (PRP) and Stem Cells. A review of published papers in PubMed's database was performed using the MESH term "sports medicine" as query, since this was considered the most adequate and broad term available according to foreign published papers. Through this method all articles available up to December 2020 were selected their relevance for this review was assessed. PRP seems to be a safe therapeutic option for some tissue treatment and healing in sports lesions. This is a promising therapy with a low potential for adverse reactions since it uses autologous tissue. Stem Cells will undoubtedly play an important role in the future of sports lesions treatment. It is known that, thus far, it has produced promising effects that have been confirmed by laboratory research and even by the natural progression of this investigation onto animal models. Hitherto, the available data allows us to assume that the use of Mesenchymatous Stem Cells will prove to be a safe option in the foreseeable future. The role that PRP and Stem Cells will play in a near future is indisputable. Albeit the promising results that they report it is still too early to ascertain with full confidence in what situations these techniques can be used with a proven benefit. Thenceforth it is imperative that clinical trials aimed at studying this possibility are performed, coupled with an adequate rehabilitation that is adapted not only to the lesion but to the overall patient's condition.